Constructing social realities of adaptation: A q-methodological study of belonging, cultural strain, and onward migration intentions among international students in South Korea - Feyissa, Israel Fisseha; Ali , Sofia Senbit (Journal of International Students, 2026)
This study examines how international students in South Korea construct subjective realities of adaptation, cultural strain, and intentions to migrate onward. Using Q-methodology, a 42-item Q-set derived from coping theory and student narratives was sorted by sixty-one participants, revealing four patterned viewpoints: Engaged Cultural Adapters, Strained but Hopeful Strivers, Burdened and Outward-Looking Copers, and Supported but Selectively Engaged Settlers. Consensus statements indicated shared difficulties around Korean-language confidence, forming close Korean friendships, and unevenly perceived institutional support. Distinguishing statements highlighted divergent interpretations regarding cultural similarity, academic pressure, career prospects, and the feasibility of long-term settlement. The findings show that adaptation is shaped not only by stressors but also by the meanings students attach to their daily academic and social environments. The study advances the theoretical understanding of the socially constructed nature of adaptation and offers practical implications for improving support, integration, and retention within South Korean higher education.